Orthopedic rehabilitation of patients with generalized forms of pathological erasure of hard tooth tissues, complicated by defects in dental rows with the use of dental implantation - Struk, V. (Actual Dentistry, 2018)
Resume. Pathological abrasion is defined as a rapidly progressive pathological process accompanied by severe loss of enamel and dentin, aesthetic, phonetic and functional disorders of the dento-jaw system, which progresses with defects in the dentition. Orthopedic rehabilitation of patients with pathological erasure of hard dental tissues should be carried out in a complex manner taking into account individual morpho-functional disorders. The gradual loading of the dental implant, in conditions of increased occlusal load, contributes to prevention of its overload at the adaptation and rehabilitation stage and prolongation of the service life of the orthopedic structure as a whole. Goal. Increasing the effectiveness of orthopedic treatment of patients with pathological erasure of hard tooth tissues and included dentition defects with non-removable dental prosthesis using the method of dental implantation. Material and methods of research. Clinical, laboratory examination and orthopedic treatment of 72 patients with common pathological erasure of hard tooth tissues aged from 35 to 65 years, women 39 and men were carried out 33. Among the special research methods, the analysis of diagnostic models, radiography (orthopantomography and computed tomography) were used. To assess the stability of implants, the frequency-resonance analysis method using the Osstell ISQ instrument was used. Results. The treatment was carried out in a complex manner, taking into account the causative factor, general health status, age of the patient, activity of the course of the pathological process by restoring the anatomical form of the teeth and replacing defects in the dentition with orthopedic structures based on dental implants. Dental implantation in the area of dentition defects was carried out with sufficient bone tissue and lack of indications for bone augmentation. During the first month after implant placement, the decline of stability in the bone-implant connection was noted, then in the second and third months after the operation, the stability of the implant was increased, reaching the maximum values for the year, indicating bone remodeling around the implant. Conclusions. Pathological erasure of hard tissues of teeth is accompanied by a number of morpho-functional changes in the dentoalveolar system, which depend on the degree of pathological erasure and are burdensome with partial loss of teeth. The method of treatment should be chosen depending on the clinical form, severity of pathology and the presence of concomitant complications. Gradual loading of the dental implant in conditions of increased occlusal load contributes to prevention of its overload at the adaptation and rehabilitation stage and prolongation of the service life of the orthopedic structure as a whole. Key words: pathological erasure of hard tissues of teeth, dental implantation.